Spatiotemporal variability of carbon dioxide (CO2) and methane (CH4) concentration and flux in the Lower Amazon region - Araújo, Maria Gabriella da Silva (2024)
This research investigates the spatiotemporal variability of carbon dioxide (CO2) and methane (CH4) concentrations and fluxes in the Lower Amazon River. The study aims to understand the hydrodynamic and biogeochemical factors driving the emission of these greenhouse gases, emphasizing their roles in global carbon cycling. The primary objectives are to identify key environmental factors, such as water velocity, channel depth, and organic matter content, that regulate gas production and evasion across different sample stations, from Óbidos to its mouth, and seasons of the river. The methodology involved extensive sampling carried out over nine field campaigns between 2014 and 2023. These campaigns covered all hydrological phases: rising, falling, high, and low water levels. Sampling took place at six key sites along the Lower Amazon River, measuring environmental parameters, including water depth, velocity, temperature, and wind speed. Gas concentrations were collected using a headspace equilibration method, while gas flux was measured using floating chambers. Generalized linear mixed models (GLMMs) were employed to analyze the complex interactions between these environmental variables and the concentrations and fluxes of CO2 and CH4. The findings indicate significant seasonal and spatial variation in both gases. Water velocity and channel depth emerged as the primary drivers of CO2 and CH4 dynamics. CO2 concentrations and fluxes increased markedly during the high-water season, with tidal effects amplifying these patterns. Methane, although more stable than CO2, exhibited some variability, particularly during the low-water period. Suspended sediment concentrations and organic matter also played crucial roles, influencing gas production through microbial processes. Spatially, the study found that CO2 concentrations and fluxes decreased progressively as the river approached the ocean, particularly in the Bailique and Chaves regions, where tidal influences are strongest. These decreases were linked to a reduction in water velocity and channel depth, factors that also influenced CH4 distribution but to a lesser degree. Seasonal patterns further revealed that both gases exhibited heightened evasion fluxes during high-water periods, driven by increased river discharge and tidal dynamics. The study highlights the complexity of gas dynamics in the Lower Amazon, where hydrodynamic factors like river discharge and tidal flow interact with biogeochemical processes to regulate greenhouse gas emissions. These emissions, particularly CO2, are exacerbated during the high-water season when river discharge increases, contributing to a significant release of carbon into the atmosphere. Additionally, the study points out the importance of understanding methane dynamics, which are influenced by water depth and oxygen levels, affecting its production and oxidation. In conclusion, the research underscores the need for continuous monitoring and an integrated approach to modeling carbon emissions in tropical river systems. The Lower Amazon, due to its unique hydrodynamics, plays a critical role in global greenhouse gas budgets, and improved emission estimates are essential for better understanding and mitigating climate change impacts. The findings call for further exploration of the influence of climate, land use, and riverine processes on carbon cycling in large tropical rivers.